2021
DOI: 10.1111/ppc.12970
|View full text |Cite
|
Sign up to set email alerts
|

Reflection of nurses' moral intelligence levels on care behaviors

Abstract: Purpose Moral intelligence is an important parameter that forms the basis and cornerstone of ethics in nursing. It is necessary to determine whether moral intelligence is reflected in the care that forms the basis of nursing. This study was carried out with the aim of determining the reflections of nurses' moral intelligence levels on their care behaviors. Findings This study was descriptive and cross‐sectional in nature. The study's sample size is 200 nurses. A personal Information Form, Moral Intelligence Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
(19 reference statements)
0
6
0
4
Order By: Relevance
“…The mean total moral intelligence scale score of the participants of this study was 201.22 ± 21.99, which indicated that they had a good level of moral intelligence. In nursing practices, love, kindness, compassion, effective interaction, honesty, discipline, and respect for human values, dignity, and rights are an indication of competence (Karabey, 2021; Üzar Özçetin & Hiçdurmaz, 2018). Additionally, considering that the profession of nursing, which is a caregiving occupation with a high moral aspect, aims to provide what is best for the patient on the basis of reasoning and conscience in care and treatment practices (Cerit et al, 2021; Üzar Özçetin & Sarıoğlu, 2021), the good level of moral intelligence among the nurses participating in this study may be evaluated as a positive finding.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean total moral intelligence scale score of the participants of this study was 201.22 ± 21.99, which indicated that they had a good level of moral intelligence. In nursing practices, love, kindness, compassion, effective interaction, honesty, discipline, and respect for human values, dignity, and rights are an indication of competence (Karabey, 2021; Üzar Özçetin & Hiçdurmaz, 2018). Additionally, considering that the profession of nursing, which is a caregiving occupation with a high moral aspect, aims to provide what is best for the patient on the basis of reasoning and conscience in care and treatment practices (Cerit et al, 2021; Üzar Özçetin & Sarıoğlu, 2021), the good level of moral intelligence among the nurses participating in this study may be evaluated as a positive finding.…”
Section: Discussionmentioning
confidence: 99%
“…The mean total moral intelligence scale score of the participants of this study was 201.22 ± 21.99, which indicated that they had a good level of moral intelligence. In nursing practices, love, kindness, compassion, effective interaction, honesty, discipline, and respect for human values, dignity, and rights are an indication of competence (Karabey, 2021;Üzar Özçetin & Hiçdurmaz, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations